Mass culture, media criminology and the stigmatization of the criminal - Teixeira, Priscila Peclat Gonçalves (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2021)
In the midst of great insatisfaction with national criminality rates, this article discusses the relationship between media’s content on criminology and mass culture, to the extent on which common belief influences the perfect duty perception. In that way, society outlooks for more severe punishments, some not bidden by law, to those stereotyped as criminals, referring to the cliche "good thief is dead thief". It aims legislation known as bland, or rather appropriate to human rights, to not be enforced and instead be replaced for private vengeance outside the state’s authority control. Incidental to this scenario, surges an ideology that incarceration and police reinforcement will solve national violence, in opposition to penalty’s finalities adopted by our legal system.